Deteksi Kelonggaran Baut Dengan Menggunakan Sinyal Suara - Fajar Dwi Junianto; Feblil Huda (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
Bolt is one of machine elements which used in joining process. Failure that often occurs in the bolt joint is usually caused by dynamic load. In this research, bolt loosening detection method by using sound signal was investigated, for that purpose by analyze the dynamic characteristics of bolt connection which are the natural frequency and damping ratio. The research method was used Structural Health Monitoring (SHM) is a process of identifying damage by Nondestructive Evaluation (NDE). The advantage this method it is not costly to set-up testing. Excitation was given to the steel plate by the speaker and the sound response of the bolt loosening was recorded through the microphone. Sound signals are given for normal bolt conditions, looseness of 1 bolt with different torque fastening variations. Sound signal data was processed using the Fast Fourier Transform (FFT) to obtain natural frequency and damping ratio. The result of this research was the value of natural frequency and damping ratio increases with the addition of bolt tightening torque.Keywords: bolt looseness, structural health monitoring (SHM), fast fourier transform (FFT)